Influenza A Viruses in Ruddy Turnstones (Arenaria interpres); Connecting Wintering and Migratory Sites with an Ecological Hotspot at Delaware Bay - Rebecca Poulson; Deborah Carter; Shelley Beville; Lawrence Niles; Amanda Dey; Clive Minton; Pamela McKenzie; Scott Krauss; Richard Webby; Robert Webster; David E. Stallknecht (Viruses, 2020)
Each May for over three decades, avian influenza A viruses (IAVs) have been isolated from shorebirds and gulls (order Charadriiformes) at Delaware Bay (DE Bay), USA, which is a critical stopover site for shorebirds on their spring migration to arctic breeding grounds. At DE Bay, most isolates have been recovered from ruddy turnstones (Arenaria interpres), but it is unknown if this species is involved in either the maintenance or movement of these viruses outside of this site. We collected and tested fecal samples from 2823 ruddy turnstones in Florida and Georgia in the southeastern United States during four winter/spring sample periods—2010, 2011, 2012, and 2013—and during the winters of 2014/2015 and 2015/2016. Twenty-five low pathogenicity IAVs were recovered representing five subtypes (H3N4, H3N8, H5N9, H6N1, and H12N2). Many of these subtypes matched those recovered at DE Bay during the previous year or that year’s migratory cycle, suggesting that IAVs present on these southern wintering areas represent a source of virus introduction to DE Bay via migrating ruddy turnstones. Analyses of all IAV gene segments of H5N9 and H6N1 viruses recovered from ruddy turnstones at DE Bay during May 2012 and from the southeast during the spring of 2012 revealed a high level of genetic relatedness at the nucleotide level, suggesting that migrating ruddy turnstones move IAVs from wintering grounds to the DE Bay ecosystem.